Preparation method of oxygen reduction catalyst of copper-iron metal organic framework

The oxygen reduction catalyst of copper-iron metal organic frame was synthesized by two-step hydrothermal method, which solved the problem of low reaction efficiency of MFC cathode and achieved the effect of significantly improving the redox performance and power generation performance of MFC.

CN119775581APending Publication Date: 2025-04-08WEIFANG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963653.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing microbial fuel cells (MFCs) have bottlenecks in improving cathode reaction efficiency, affecting their power production performance.

Method used

The oxygen reduction catalyst of the copper-iron metal organic frame was synthesized by a simple two-step hydrothermal method. The iron-iron organic frame and the copper-iron organic frame were combined through in-situ synthesis to form a catalyst with a regular cylindrical crystal and a dense surface sheet structure.

Benefits of technology

It significantly improves the redox performance and power generation performance of MFC, improves electron transfer efficiency, and optimizes the overall efficiency of microbial fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775581A_ABST
    Figure CN119775581A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a redox catalyst of a copper-iron metal organic framework, which comprises the following steps: taking a copper metal organic framework as a substrate, fusing octahedral iron metal organic framework copper to form a regular cylindrical crystal, and fully distributing sheet structures on the surface, thereby successfully preparing the copper-iron metal organic framework. The material is used as a cathode catalyst of a microbial fuel cell, and by virtue of rich active sites and excellent conductivity of the material, the transmission efficiency of electric ions is remarkably improved, the lasting stability of an electrode is enhanced, and the power generation efficiency is greatly improved. The innovative application not only optimizes the overall performance of the fuel cell, but also opens up a new breakthrough point for the field of energy conversion and storage, and shows huge application potential and value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cathode modification of microbial fuel cells, and in particular to a method for preparing a copper-iron metal organic framework oxygen reduction catalyst. Background Art

[0002] The rapid development of science and technology and the rapid progress of social civilization have greatly promoted the transformation and prosperity of human society, but at the same time, it has also led to an increasing demand for various resources. Microbial fuel cells (MFC), as a new type of energy conversion device in the field of wastewater treatment technology, have gradually emerged in this field and become a hot topic of research due to their unique advantages.

[0003] MFC directly converts chemical energy in organic matter into electrical energy by utilizing the catalytic action of microorganisms. This process not only effectively removes organic pollutants in wastewater, but also simultaneously generates clean energy, truly turning waste into treasure. This technology not only improves resource utilization efficiency and reduces treatment costs, but also reduces greenhouse gas emissions. However, the power generation performance of MFC is affected by many complex factors, including substrates, microorganisms, membrane materials, electrode characteristics and their design, electrolytes, reactor design, temperature, pH value, and extracellular electron transfer. Among them, improving the efficiency of cathode reactions is the key bottleneck. Selecting a suitable cathode catalyst is crucial to reducing the reduction potential and improving the redox efficiency, and is the key to promoting the more efficient and environmentally friendly development of MFC. Optimizing the types and performance of catalysts is expected to open up new paths for improving MFC performance and inject new vitality into the energy field.

[0004] In response to the above problems, a large number of studies have found that metal organic framework (MOF) materials have become a hot topic in microbial fuel cell research due to their rich pore structure and more reaction sites. MOF is an advanced organic-inorganic hybrid material. They are characterized by the self-assembly of metal ions and carefully designed organic ligands. This self-assembly occurs through precise coordination bonds, constructing a complex structure with rich molecular-level porosity. These MOFs present different shapes. They range from micrometers to nanometers, such as spheres, cubes, sheets, and rods. They also have unique chemical multifunctionality. This versatility stems from the diversity of their pore structures in size, type, and distribution. However, in the power generation application of MFC, low conductivity and large steric hindrance have become two major obstacles for MOF materials to be directly used as electrode materials, which limits their performance. Therefore, it is particularly important to explore new strategies to enhance the inherent electrocatalytic properties of MOF materials. Although some scholars have tried to improve their activity by combining MOF with MOF, research in this field is still relatively small, and the synthesized composite materials still face some challenges and problems in practical applications.

[0005] Therefore, it is necessary to propose further solutions to the above problems. Summary of the invention

[0006] The present invention aims to provide a method for preparing a copper-iron metal organic framework oxygen reduction catalyst. The prepared microbial fuel cell cathode catalyst can effectively improve the power generation performance of MFC.

[0007] The technical solution of the present invention is: A method for preparing a copper-iron metal organic framework oxygen reduction catalyst, the method comprising the following steps: Step 1: First, 2.2091 g FeCl 3 6H 2 O and 2.075 g terephthalic acid (H 2 BDC) was stirred in 150 mL N,N-dimethylformamide (DMF) to obtain a clear solution to prepare the iron metal organic framework. Subsequently, the obtained solution was transferred to a Teflon-lined stainless steel autoclave with a capacity of 200 mL and heated at 110°C for 24 h. After cooling to room temperature, it was washed with ethanol and then vacuum dried at 60°C overnight to obtain a yellow product iron metal organic framework.

[0008] Step 2: 0.5 g Fe-MOF and 1.6854 g Cu (NO 3 ) 2 ·3H 2 O was ultrasonically reacted with 1.2228 g of aminoterephthalic acid, 150 mL of DMF and 2.25 mL of acetic acid were added, heated at 150 °C for 5 h, naturally cooled, centrifuged, washed with ethanol, and dried at 60 °C for 24 h to synthesize the CuFe-MOF.

[0009] Furthermore, the stirring in step 1 is stirring at room temperature for 0.5 h.

[0010] Furthermore, the heating in step 1 is to heat the reactor to 110° C. in an oven and maintain it for 24 h.

[0011] Furthermore, the drying in step 1 should be performed at 60° C. for 12 h.

[0012] Furthermore, the ultrasonication in step 2 is carried out at room temperature for 0.5 h.

[0013] Furthermore, the heating in step 2 is to heat the reactor to 150° C. in an oven and maintain it for 5 h.

[0014] Furthermore, the drying in step 2 should be performed at 60° C. for 24 h.

[0015] The present invention provides a method for preparing a copper-iron metal organic framework oxygen reduction catalyst, and the copper-iron metal organic framework is synthesized by a simple two-step hydrothermal method. First, the iron metal organic framework is synthesized, and the iron metal organic framework is combined with the copper metal organic framework by in-situ synthesis to form a copper-iron metal organic framework having regular cylindrical crystals and a densely flaky structure on the surface. This synthesis process is not only simple to operate and easy to implement, but the synthesized copper-iron metal organic framework crystals are rich in active sites, which significantly improves the efficiency of electron transfer. Experimental results show that the copper-iron metal organic framework not only exhibits excellent power generation performance, but also greatly optimizes the redox performance of microbial fuel cells. In order to further explore its application potential, we used stainless steel wire mesh (SS) as a substrate and adopted a double-layer polytetrafluoroethylene (PTFE) treatment technology to prepare a copper-iron metal organic framework microbial fuel cell cathode. Through a series of performance tests, the influence of the cathode on the performance of microbial fuel cells was deeply studied, confirming its significant role in improving the efficiency of microbial fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic flow diagram of the preparation method of the copper-iron metal organic framework oxygen reduction catalyst of the present invention; Figure 2 This is a SEM image of the preparation method of the copper-iron metal organic framework oxygen reduction catalyst of the present invention; Figure 2 (a) is a scanning electron microscope image of Fe-MOF; Figure 2 (b) is a scanning electron microscope image of Cu-MOF. Figure 2 (c) Figure 2 (d) is the scanning electron microscope image of Cu-MOF@Fe-MOF; Figure 3 XRD graph (a) and FTIR graph (b) of Fe-MOF, Cu-MOF, and Cu-MOF@Fe-MOF in the preparation method of the copper-iron metal organic framework oxygen reduction catalyst of the present invention; Figure 4 CV curves (a) and LSV curves (b) of Fe-MOF, Cu-MOF, and Cu-MOF@Fe-MOF as cathode catalysts for microbial fuel cells in the method for preparing the copper-iron metal organic framework oxygen reduction catalyst of the present invention; Figure 5 The EIS curves of Fe-MOF, Cu-MOF, and Cu-MOF@Fe-MOF as cathode catalysts for microbial fuel cells in the method for preparing the copper-iron metal organic framework oxygen reduction catalyst of the present invention are shown; Figure 6The invention relates to the method for preparing the copper-iron metal organic framework oxygen reduction catalyst of the present invention, and the power density curves of the cathode catalysts of Fe-MOF, Cu-MOF and Cu-MOF@Fe-MOF microbial fuel cells when the voltage is stable. DETAILED DESCRIPTION

[0017] The present invention is further described in detail below in conjunction with specific implementation modes.

[0018] See also Figure 1 , Figure 1 FIG. 1 is a schematic flow diagram of a method for preparing a copper-iron metal organic framework oxygen reduction catalyst according to the present invention. Figure 1 As shown, the present invention provides a method for preparing a copper-iron metal organic framework oxygen reduction catalyst, comprising the following steps: Step 1: First, 2.2091 g FeCl 3 6H 2 O and 2.075 g terephthalic acid (H 2 BDC) was stirred in 150 mL N,N-dimethylformamide (DMF) to obtain a clear solution to prepare the iron metal organic framework. Subsequently, the obtained solution was transferred to a Teflon-lined stainless steel autoclave with a capacity of 200 mL and heated at 110°C for 24 h. After cooling to room temperature, it was washed with ethanol and then vacuum dried at 60°C overnight to obtain a yellow product.

[0019] Step 2: 0.5 g Fe-MOF and 1.6854 g Cu (NO 3 ) 2 ·3H 2 O was ultrasonically reacted with 1.2228 g of aminoterephthalic acid, 150 mL of DMF and 2.25 mL of acetic acid were added, heated at 150 °C for 5 h, naturally cooled, centrifuged, washed with ethanol, and dried at 60 °C for 24 h to synthesize the CuFe-MOF.

[0020] After the above two steps, the oxygen reduction catalyst of the copper-iron metal organic framework is prepared. After these two steps, the structure can also be tested, such as using the sample as a cathode to test the performance of a microbial fuel cell.

[0021] Step 3: Conduct electrochemical performance tests on an electrochemical workstation using a three-electrode system, and conduct microbial fuel cell performance tests using the copper-iron metal organic framework composite material as a cathode catalyst.

[0022] The abbreviations mentioned in the present invention are all fixed abbreviations in the field, and some of the abbreviations are explained as follows: SEM: scanning electron microscope; FTIR: Fourier transform infrared spectroscopy; XRD: x-ray diffraction pattern.

[0023] Example 1 This embodiment demonstrates the implementation scheme of the copper-iron metal organic framework oxygen reduction catalyst as follows: In order to study the electrochemical performance of copper-iron metal organic framework oxygen reduction catalyst, the present invention uses iron metal organic framework, copper metal organic framework and copper-iron metal organic framework as MFC cathode catalysts. CV and LSV tests are carried out in 50 mM PBS solution.

[0024] See also Figure 4 By comparing the cyclic voltammetry curves, it can be seen that at the same scan rate, the copper metal organic framework presents two obvious redox peaks; in contrast, the CV curve of the copper iron metal organic framework composite shows two prominent oxidation peaks. This observation can be attributed to the complex phase transition that occurs during the oxidation process, resulting in the bifurcation of the oxidation peak. This split indicates that the reactivity of the material is enhanced in an electrochemical oxidizing environment. It also clarifies the potential multi-stage or structural reorganization steps that the material may undergo during the transformation process. Generally, MOF materials undergo chemical bond cleavage and reorganization during oxidation, while the valence state of the metal ions also changes. This phenomenon may lead to the bifurcation of the oxidation peak in the CV curve, providing an important understanding of the electrochemical properties and phase change mechanism of the material. In the CV curve of the copper iron metal organic framework, the reduction peak shows a significant high intensity, which is a strong indicator of the superior chemical properties of the material. The enhancement of the intensity of this reduction peak generally means an increase in the activity and efficiency of the electrochemical reduction process, thereby promoting more efficient electron transfer and promoting chemical reactions. This observation emphasizes the great potential of copper iron metal organic frameworks in energy storage and catalytic conversion applications. This also lays a solid foundation for their application in high-performance electrochemical devices.

[0025] In order to further investigate the electrocatalytic activity of the composite catalyst, the present invention investigated the LSV curves of different catalysts at a scanning rate of 10 mV / s. The results show that the order of the catalyst tilt is Cu-MOF@Fe-MOF>Cu-MOF>Fe-MOF. The slope of the voltammetric curve shows that at the same cathode potential, Cu-MOF@Fe-MOF has a larger current and a higher conductivity. Overall, the copper-iron metal organic framework oxygen reduction catalyst has good redox performance and high catalytic performance.

[0026] Example 2 This embodiment demonstrates the implementation scheme of the copper-iron metal organic framework oxygen reduction catalyst according to the following scheme: In order to study the electrochemical performance of CuFeMOF-based oxygen reduction catalysts, FeMOF, CuMOF and CuFeMOF were used as MFC cathode catalysts. EIS experiments were carried out in 50 mM PBS solution.

[0027] See also Figure 5 By comparing the electrochemical impedance spectra, it can be seen that when the initial potential is -0.5 V, in the high-frequency region, Cu-MOF@Fe-MOF has the smallest semicircle diameter, which clearly indicates that its charge transfer resistance is the lowest. This observation indicates that the electron flow between the electrode and the electrolyte is more efficient during the electrochemical process, thereby accelerating the ORR. Transitioning to the low-frequency region, the slope of Cu-MOF@Fe-MOF in this region is significantly larger, a significant feature indicating that its ion diffusion rate significantly exceeds that of the two comparative materials. The enhancement of ion diffusion promotes the rapid transport of active substances in the electrolyte. It also greatly enhances the redox ability of the material, further improving its overall electrochemical performance. In summary, the copper-iron metal organic framework has extremely small charge transfer resistance and excellent ion diffusion rate, and performs well in the electrochemical performance evaluation. It exhibits excellent redox ability and excellent electrochemical characteristics.

[0028] Example 3 This embodiment demonstrates the implementation scheme of the copper-iron metal organic framework oxygen reduction catalyst according to the following scheme: See also Figure 6 , using iron metal organic framework, copper metal organic framework, copper iron metal organic framework as the cathode catalyst of the single chamber MFC, and keeping the anode state consistent, to evaluate the effect of different cathode catalysts on the power generation capacity of MFC. By gradually reducing the external resistance of MFC (from 2200 Ω to 20 Ω), the power density curve and voltage when the voltage is stable are evaluated.

[0029] See also Figure 6 , the maximum power density produced by Cu-MOF@Fe-MOF-MFC is 231.2 mW / m², which is 2.74 times that of Fe-MOF-MFC (84.1 mW / m²) and 1.94 times that of Cu-MOF-MFC (119.1 mW / m²). This result highlights the superior electrochemical performance of Cu-MOF@Fe-MOF and emphasizes the importance of its high power density as an important indicator for evaluating its application in MFCs.

[0030] Refer to Table 1, the maximum cell voltage produced by Cu-MOF@Fe-MOF-MFC is 240 mV, followed by Cu-MOF-MFC at 190 mV, while the maximum voltage of Fe-MOF-MFC is relatively low at 128 mV. Higher voltage means faster glucose consumption, which further proves that the ORR reaction using CuFeMOF as cathode catalyst is more efficient. In addition, the output voltage of CuFeMOF MFC does not change much within 13 days, indicating that the catalyst has good durability and cycle stability.

[0031] The following are specific conclusions drawn after detailed testing and analysis of the copper-iron metal organic framework as an oxygen reduction catalyst in the above examples: See also Figure 2 The morphology and microstructure of Cu-MOF, Fe-MOF and Cu-MOF@Fe-MOF were examined by scanning electron microscopy. Figure 2 As shown. The SEM image of Fe-MOF shows an octahedral shape. Figure 2 As shown in (b), the surface of Cu-MOF shows irregularity, consisting of many rough and fluffy nanosheets. This unique structure enhances the pore distribution inside the material and provides abundant active sites for electron contact and transfer. The morphology of the Cu-MOF@Fe-MOF composite material was significantly changed by a hydrothermal synthesis process. This process transforms the material from its original form into a regular cylindrical crystal structure with sheet-like structures cleverly embedded on its surface. This arrangement provides the catalyst with a larger specific surface area to promote the efficient access of reactants to the active sites, thereby significantly improving the catalytic efficiency. In addition, the sheet-like structures loaded on the surface further increase the roughness and porosity of the catalyst, while providing an ideal pathway for rapid electron transfer and reactant penetration. This structural optimization directly promotes efficient electron transfer during the ORR process, accelerates the reaction kinetics, and exhibits excellent catalytic performance in Cu-MOF@Fe-MOF.

[0032] See also Figure 3 , Figure 3 (a) shows the XRD curves of Cu-MOF, Fe-MOF and Cu-MOF@Fe-MOF. Figure 3 (b) shows the FT-IR curves of Cu-MOF, Fe-MOF and Cu-MOF@Fe-MOF, which all indicate that Cu-MOF, Fe-MOF and Cu-MOF@Fe-MOF have been successfully prepared. Figure 3As shown in (a), for Cu-MOF, a series of sharp peaks with different intensities are observed at specific 2-theta values, corresponding to the crystal planes

[111] ,

[222] ,

[422] ,

[200] and

[220] , with angles of 10.1°, 11.7°, 16.6°, 50.2° and 74°, respectively. It is worth noting that a peak is also observed at 43.1°, corresponding to the

[111] crystal plane, which is consistent with previous studies. The XRD single crystal morphology and obvious peaks of the synthesized Cu-MOF sample indicate its high crystallinity. The XRD spectrum of Fe-MOF has a significant correspondence with the structural features of MIL-88b (Fe) (CCDC No. 1485530). The characteristic XRD peaks of Cu-MOF and Fe-MOF were observed in Cu-MOF@Fe-MOF, confirming the successful formation of the hybrid material. It is worth noting that the XRD of Cu-MOF@Fe-MOF is very similar to that of Cu-MOF, which indicates that the incorporation and modification of Fe-MOF did not cause a phase change in the Cu-MOF crystal structure. However, a decrease in the intensity of the primary diffraction peak was noted, and this reduced intensity may be attributed to being covered or filled by other substances, possibly iron hydroxide. In contrast, the decrease in the intensity of the 43.1° and 50.2° peaks is more obvious than the decrease in the intensity of the 16.6° peak. The changes in the XRD spectrum of Cu-MOF@Fe-MOF indicate that iron oxide may have penetrated into the pores of Cu-MOF rather than just covering its surface. Figure 3 (b) FT-IR was used to analyze the molecular structures of the three materials and determine whether there were chemical bonds inside the three materials. The 1500, 1374, and 756 cm-1 wavelengths observed in the Cu-MOF sample - The peaks at 1697, 1596, 1391, 748, and 541 cm-1 correspond to the stretching vibrations of the C=C, C=O, and Cu-O functional groups, respectively. The detection of these wavelengths in the infrared spectrum confirms the successful synthesis of Cu-MOF. −1 The characteristic peaks at 1253 cm-1 of Cu-MOF@Fe-MOF@Fe-MOF@Cu ...Fe-MOF@Cu-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Cu-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Cu-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Fe-MOF@Fe -1 In addition to the enhancement of the band at 1384 cm -1 and 545 cm -1 The stretching vibrations corresponding to the C=O and Fe-O groups were detected at 3100-3600 cm -1The broad bands observed in the spectral range can be attributed to the stretching vibration modes of -OH and HOH bonds, which are directly related to the water molecules adsorbed on the surface. This finding clarifies the enhanced hydrophilicity of the material surface. It also means that the interaction between the material and water molecules is strengthened, which generally means that the internal structure is more compact and ordered, thereby indirectly indicating an increase in its overall strength. This observation is consistent with the conclusions drawn from the XRD analysis, confirming that Cu-MOF, Fe-MOF, and Cu-MOF@Fe-MOF have been successfully prepared.

[0033] Compared with the prior art, the invention has the following beneficial effects: a copper-iron metal organic framework is synthesized by a simple two-step hydrothermal method. First, the iron metal organic framework is synthesized, and the iron metal organic framework is combined with the copper metal organic framework by in-situ synthesis to form a copper-iron metal organic framework oxygen reduction catalyst having regular cylindrical crystals and a densely flaky structure on the surface.

[0034] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a copper-iron metal organic framework oxygen reduction catalyst, characterized in that: The method comprises the following steps: Step 1: First, 2.2091 g FeCl3·6H2O and 2.075 g terephthalic acid were stirred in 150 mL N,N-dimethylformamide to obtain a clear solution to prepare an iron metal organic framework; then, the obtained solution was transferred to a 200 mL Teflon-lined stainless steel autoclave and heated at 110°C for 24 h; after cooling to room temperature, it was washed with ethanol and then vacuum dried at 60°C overnight to obtain a yellow product iron metal organic framework; Step 2: 0.5 g of Fe-MOF and 1.6854 g of Cu (NO3)2·3H2O were ultrasonically reacted with 1.2228 g of aminoterephthalic acid, 150 mL of DMF and 2.25 mL of acetic acid were added, heated at 150°C for 5 h, naturally cooled, centrifuged, washed with ethanol, and dried at 60°C for 24 h to synthesize the Cu-Fe-MOF.

2. The method for preparing the copper-iron metal organic framework oxygen reduction catalyst according to claim 1, characterized in that: The stirring in step 1 is stirring at room temperature for 0.5 h.

3. The method for preparing the copper-iron metal organic framework oxygen reduction catalyst according to claim 1, characterized in that: The heating in step 1 is to heat the reactor to 110° C. in an oven and maintain it for 24 h.

4. The method for preparing the copper-iron metal organic framework oxygen reduction catalyst according to claim 1, characterized in that: The drying process in step 1 should be performed at 60°C for 12 h.

5. The method for preparing the copper-iron metal organic framework oxygen reduction catalyst according to claim 1, characterized in that: The ultrasonic treatment in step 2 is carried out at room temperature for 0.5 h.

6. The method for preparing the copper-iron metal organic framework oxygen reduction catalyst according to claim 1, characterized in that: The heating in step 2 is to heat the reactor to 150° C. in an oven and maintain it for 5 h.

7. The method for preparing the copper-iron metal organic framework oxygen reduction catalyst according to claim 1, characterized in that: The drying in step 2 should be performed at 60°C for 24 h.

8. An oxygen reduction catalyst of a copper-iron metal organic framework prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the copper-iron metal organic framework oxygen reduction catalyst according to claim 8 in a microbial fuel cell.